A Pediatric Tumor Found Frequently in the Adult Population: A Case of Anaplastic Astroblastoma in an Elderly Patient and Review of the Literature - Christopher Payne; Ali Batouli; Kristen Stabingas; Dunbar Alcindor; Khaled Abdel Aziz; Cunfeng Pu; Elizabeth Tyler-Kabara; Robert Williams; Alexander Yu (Case Reports in Neurological Medicine)
Astroblastomas are rare, potentially curable primary brain tumors which can be difficult to diagnose. We present the case of astroblastoma in a 73-year-old male, an atypical age for this tumor, more classically found in pediatric and young adult populations. Through our case and review of the literature, we note that this tumor is frequently reported in adult populations and the presentation of this tumor in the elderly is well described. This tumor is an important consideration in the differential diagnosis when managing both pediatric and adult patients of any age who present with the imaging findings characteristic of this rare tumor.